Post-standardization of routine creatinine assays: are they suitable for clinical applications. (May 2017) - Jassam, Nuthar; Weykamp, Cas; Thomas, Annette; Secchiero, Sandra; Sciacovelli, Laura; Plebani, Mario; Thelen, Marc; Cobbaert, Christa; Perich, Carmen; Ricós, Carmen; Paula, Faria A; Barth, Julian H
Introduction: Reliable serum creatinine measurements are of vital importance for the correct classification of chronic kidney disease and early identification of kidney injury. The National Kidney Disease Education Programme working group and other groups have defined clinically acceptable analytical limits for creatinine methods. The aim of this study was to re-evaluate the performance of routine creatinine methods in the light of these defined limits so as to assess their suitability for clinical practice. Method: In collaboration with the Dutch External Quality Assurance scheme, six frozen commutable samples, with a creatinine concentration ranging from 80 to 239 μ mol/L and traceable to isotope dilution mass spectrometry, were circulated to 91 laboratories in four European countries for creatinine measurement and estimated glomerular filtration rate calculation. Two out of the six samples were spiked with glucose to give high and low final concentrations of glucose. Results: Results from 89 laboratories were analysed for bias, imprecision (%CV) for each creatinine assay and total error for estimated glomerular filtration rate. The participating laboratories used analytical instruments from four manufacturers; Abbott, Beckman, Roche and Siemens. All enzymatic methods in this study complied with the National Kidney Disease Education Programme working group recommended limits of bias of 5% above a creatinine concentration of 100 μ mol/L. They also did not show any evidence of interference from glucose. In addition, they also showed compliance with the clinically recommended %CV of ≤4% across the analytical range. In contrast, the Jaffe methods showed variable performance with regard to the interference of glucose and unsatisfactory bias and precision. Conclusion: Jaffe-based creatinine methods still exhibit considerable analytical variability in terms of bias, imprecision and lack of specificity, and this variability brings into question their clinical utility. We believe that clinical laboratories and manufacturers should work together to phase out the use of relatively non-specific Jaffe methods and replace them with more specific methods that are enzyme based.